2009
DOI: 10.4489/myco.2009.37.2.082
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Associated with the Hairs of Goat and Sheep in Libya

Abstract: The mycoflora on the hair in 25 samples of each of goats and sheep collected from Libya was analyzed using two isolation methods at 25℃. Seventy species and 3 varieties belonging to 31 genera were collected from the two substrates. The hairs of sheep were polluted with fungi than goat, contained high total counts and number of genera and species. Two species of true dermatophytes were isolated namely Trichophyton rubrum and T. terrestre. Several keratiophilic species were isolated of which Chrysosporium indicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(62 reference statements)
2
16
0
Order By: Relevance
“…Various saprophytic fungi were encountered and the most prevalent species on the goat sheep were members of Aspergillus, Penicillium, Alternaria and Cochliobolus. These results are similar to those obtained by El-Said and Abdel-Sater (1995) and El-Said et al (2009). They reported that members of Aspergillus, Penicillium, Alternaria and Cochliobolus were the most common in order of frequency, saprophytic fungi from goat and sheep hairs in El-Bahrain and Libya.…”
Section: Saprophytic Fungi (Using Glucose-czapek's Agar)supporting
confidence: 90%
See 4 more Smart Citations
“…Various saprophytic fungi were encountered and the most prevalent species on the goat sheep were members of Aspergillus, Penicillium, Alternaria and Cochliobolus. These results are similar to those obtained by El-Said and Abdel-Sater (1995) and El-Said et al (2009). They reported that members of Aspergillus, Penicillium, Alternaria and Cochliobolus were the most common in order of frequency, saprophytic fungi from goat and sheep hairs in El-Bahrain and Libya.…”
Section: Saprophytic Fungi (Using Glucose-czapek's Agar)supporting
confidence: 90%
“…The most contaminated hairs were that of sheep with the higher total counts (226 isolates/300 fragments) and a wide spectrum of species (14 species) than that of goat (174 isolates and 13 species) as shown in Table 1. Similar observations were obtained from goats and sheep in many parts of the world (Nasser and Abdel-Sater, 1997;El-Said et al, 2009;Sallam and ALKolaibe, 2010). Chrysosporium was the most frequent genus and emerged in 90 and 96.6% of the samples comprising 83.3 and 80.5% of total isolates and have relative importance value RIV of 173.3 and 177.1 of goat and sheep, respectively.…”
Section: Dermatophytic and Keratinophilic Fungi (Using Hair Baiting Tsupporting
confidence: 79%
See 3 more Smart Citations